Pathogenic Variations of Homologous Recombination Gene HSF2BP Identified in Sporadic Patients With Premature Ovarian Insufficiency - Li, Shan; Xu, Weiwei; Xu, Bingying; Gao, Shuchang; Zhang, Qian; Qin, Yingying; Guo, Ting (Frontiers in Cell and Developmental Biology, 2022)
Premature ovarian insufficiency (POI) is defined as depletion of ovarian function before 40 years of age, which affects 3.7% of women in reproductive age. The etiology of POI is heterogenous. Recently, with the widespread use of whole exome sequencing (WES), the DNA repair genes, especially for those involved in meiosis progress, were enriched in the causative gene spectrum of POI. In this study, through the largest in-house WES database of 1,030 patients with sporadic POI, we identified two novel homozygous variations in HSF2BP (c.382T>C, p.C128R; c.557T>C, p.L186P). In vitro functional study revealed that both variations impaired the nuclear location of HSF2BP and affected its DNA repair capacity for DNA double strand breaks. Our studies highlighted the essential role of meiotic homologous recombination genes in the pathogenesis of sporadic POI.